The ATEAM study: Advances in technology to enhance PrEP adherence monitoring (ATEAM) among young men who have sex with men - Jennifer Brothers; Sybil Hosek; Kody Keckler; Peter L. Anderson; Di Xiong; Honghu Liu; Gregory Huhn (Wiley, 2022)
Abstract Young age has consistently correlated with lower adherence to pre‐exposure prophylaxis (PrEP) in young men who have sex with men (YMSM). Digital medicine, a dynamic healthcare platform of wearable physiological sensors and mobile communication technology that can respond to medication nonadherence rapidly, has the potential in promoting PrEP adherence. We evaluated the feasibility and acceptability of Proteus Discover, a digital monitoring adherence system, to measure PrEP adherence and provide real‐time feedback among cisgender YMSM and transgender women. One hundred HIV‐negative young men and transgender women ages 16-24 years were enrolled in a 24‐week randomized controlled crossover study to tenofovir disoproxil fumarate with emtricitabine (TDF/FTC) coencapsulated with Proteus Discover versus TDF/FTC standard‐of‐care. Participants in the 12‐week Proteus Discover arm received weekly SMS text messages to promote pill taking based on Proteus Discover adherence data. Dried blood spots (DBS) were collected at 4‐week intervals for tenofovir diphosphate (TFV‐DP) in red blood cells as the referent and questionnaires were completed to assess acceptability, usability, and patterns of use. Linear mixed models analyzed the relationship between 30‐day adherence measured by DBS and Proteus Discover. PrEP adherence was high overall. Adherence, as measured by DBS, was correlated with adherence as measured by Proteus Discover (p value = 0.03). Most participants reported that Proteus Discover helped them take their PrEP daily and that the system was easy to use. However, a majority (53.5%-60.5%) disagreed with the statement that wearing the patch was not an issue. There was an incremental increase in TFV‐DP in DBS with adherence by Proteus Discover. More research is warranted to explore optimizing PrEP adherence for youth through real‐time monitoring.